2017
DOI: 10.1088/1757-899x/207/1/012083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerodynamic fairing on full scale blade fatigue test

Abstract: Abstract.The reliability of large blades should be verified by means of full scale fatigue test. In order to solve the problem of lack of exciting force during fatigue test in the flap wise direction, the program that aerodynamic fairing is installed in the tip of blade to reduce the air resistance is proposed. The numerical model of blade vibration and damping ratio calculation is established. The relationship between damping ratio, exciting force and amplitude is constructed by finite element method respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…This occurs due to high aerodynamic damping resulting from the flapwise motion. Combining the biaxial test with aerodynamic fairings, as proposed by Pan et al (2017), the damping may be reduced and less force would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs due to high aerodynamic damping resulting from the flapwise motion. Combining the biaxial test with aerodynamic fairings, as proposed by Pan et al (2017), the damping may be reduced and less force would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical gradient of the bending moment is 2%. The frequency distribution of each bending moment is converted into a cumulative equivalent bending moment according to Equation (16). Figure 15 depicts the comparison of the spatial damage distribution with the target distribution for single-point excitation and dual-point excitation.…”
Section: Fatigue Test Of the Equivalent Life Cyclementioning
confidence: 99%
“…White [14,15] developed a new hybrid fatigue testing system called the Blade Resonance Excitation (B-REX) test system, which used 65% less energy to test large wind turbine blades in half the time of NREL's (National Renewable Energy Laboratory) dual-axis forced-displacement test method, with lower equipment and operating costs. Pan [16] found that aerodynamic fairing installed in the tip of the blade could reduce air resistance; the results showed that the required exciting force could be decreased by 45.4% when the target equivalent fatigue damage was reached. Zarouchas [17] numerically and experimentally investigated the prismatic composite I-beams and the mechanical behavior of adhesive bond lines.…”
Section: Introductionmentioning
confidence: 99%